2004
DOI: 10.1369/jhc.3a6136.2004
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Unique and Developmental Myosin Heavy Chain Isoforms in Adult Human Digastric Muscle

Abstract: Digastric muscle (DGM) is a powerful jaw-opening muscle that participates in chewing, swallowing, breathing, and speech. For better understanding of its contractile properties, five pairs of adult human DGMs were obtained from autopsies and processed with immunocytochemistry and/or immunoblotting. Monoclonal antibodies against alpha-cardiac, slow tonic, neonatal, and embryonic myosin heavy chain (MHC) isoforms were employed to determine whether the DGM fibers contain these MHC isoforms, which have previously b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
27
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 44 publications
7
27
2
Order By: Relevance
“…Although this fiber type classification scheme has been demonstrated to correlate well with histochemical, biochemical, and physiological characteristics of different skeletal muscle fibers, its use in the fiber typing for the specialized cranial muscles may be limited. Our studies Wang et al, 2004;present study) and others have demonstrated that some cranial muscles contain unusual MHC isoforms. The presence or absence of the unusual MHC isoforms in the cranial muscle fibers cannot be detected by mATPase histochemistry.…”
Section: Fiber-type Classification For Cranial Musclessupporting
confidence: 67%
“…Although this fiber type classification scheme has been demonstrated to correlate well with histochemical, biochemical, and physiological characteristics of different skeletal muscle fibers, its use in the fiber typing for the specialized cranial muscles may be limited. Our studies Wang et al, 2004;present study) and others have demonstrated that some cranial muscles contain unusual MHC isoforms. The presence or absence of the unusual MHC isoforms in the cranial muscle fibers cannot be detected by mATPase histochemistry.…”
Section: Fiber-type Classification For Cranial Musclessupporting
confidence: 67%
“…For example, MHC-toncontaining fibers common in lower vertebrates and birds (Hess 1970) have been found in extraocular muscles (Pierobon-Bormioli et al 1979;Sartore et al 1987), middle ear (Mascarello et al 1982), laryngeal muscles , masseter Ren and Mu 2005), suprahyoid muscles Wang et al 2004;Ren and Mu 2005), UES (present study), and in muscle spindles .…”
Section: Discussionsupporting
confidence: 55%
“…MHC-a, one of the major isoforms in the heart, has been identified in extraocular muscles (Wieczorek et al 1985;Pedrosa-Domellof et al 1992;Rushbrook et al 1994;Rubinstein and Hoh 2000), masseter (Bredman et al 1991;Pedrosa-Domellof et al 1992;Stal et al 1994;Kwa et al 1995;Korfage et al 2000;Mu et al 2004;Ren and Mu 2005), suprahyoid muscles Wang et al 2004;Ren and Mu 2005), UES (present study), and in muscle spindles (Michel et al 1996).…”
Section: Discussionsupporting
confidence: 55%
“…The three major MHCs in the muscle fibers were detected using ABC method as described (Mu et al, , 2007aWang et al, 2004;Ren and Mu, 2005;Mu and Sanders, 2007). Briefly, the serial cross-sections were (1) fixed in 4% paraformaldehyde for 10 min; (2) blocked in 2% bovine serum albumin (BSA) with 0.1% Triton X-100 for 20 min; (3) incubated with primary mAbs for 1 hr at room temperature (mAb NOQ7-5-4D) or overnight at 48C (mAbs MY-32 and SC-71); (4) incubated with a Vectastain anti-mouse IgG (ATCC, Rockville, MD) for 1 hr and reacted in ABC reagent for 1 hr; (5) reacted for 10 min with a solution containing 3,3 0 -diaminobenzidine (DAB) as chromogen to localize peroxidase for primary antibodies according to DAB substrate kit (SK-4100; Vector Laboratories, Burlingame, CA); and (6) dehydrated in graded concentrations of ethanol, cleared in xylene, and mounted with Permount.…”
Section: Histological and Immunocytochemical Proceduresmentioning
confidence: 99%
“…The unusual MHC isoforms in the muscle fibers were detected using indirect immunofluorescent staining as described (Mu et al, , 2007aWang et al, 2004;Ren and Mu, 2005;Mu and Sanders, 2007). Briefly, the sections adjacent to those stained with the ABC method were (1) fixed in 4% fresh paraformaldehyde for 10 min; (2) blocked in 2% BSA with 0.1% Triton X-100 for 20 min; (3) incubated with primary mAbs at 48C for either 12 hr (mAbs N2.261 and F1.652) or 24 hr (mAbs ALD-58 and BA-G5); (4) blocked again with 1% BSA for 5 min; (5) incubated in a fluorescein isothiocyanate-labeled goat anti-mouse IgG (FITC-GAM; 1:50 dilution; Sigma, St Louis, MO) for 1 hr; and (6) mounted with Vectashield mounting medium (Vector Laboratories) and kept in the dark at 48C.…”
Section: Histological and Immunocytochemical Proceduresmentioning
confidence: 99%